2017
DOI: 10.1007/s10549-017-4142-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of BRCA1/2 mutations carriers including large genomic rearrangements in high risk breast cancer patients

Abstract: PurposeWe investigated the prevalence of BRCA1/2 small mutations and large genomic rearrangements in high risk breast cancer patients who attended a genetic counseling clinic.MethodsIn total 478 patients were assessed for BRCA1/2 mutations by direct sequencing, of whom, 306 were identified as non-carriers of BRCA1/2 mutation and assessed for large rearrangement mutations by multiplex ligation-dependent probe amplification. Family history and clinicopathological characteristics of patients were evaluated.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
8
1
1
Order By: Relevance
“…Other variants that also lead to skipping of exon 23 have been published as pathogenic, e.g. c.5407-2A>G [11,26], c.5407-10G>A [27], c.5467+1G>A [28] and c.5434C>G (p.Pro1812Ala) [11,29]. Although a wide range of alternative transcripts have been described for the BRCA1 locus [12], there were no signs of aberrant splicing of exon 23 among the 30 normal controls in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Other variants that also lead to skipping of exon 23 have been published as pathogenic, e.g. c.5407-2A>G [11,26], c.5407-10G>A [27], c.5467+1G>A [28] and c.5434C>G (p.Pro1812Ala) [11,29]. Although a wide range of alternative transcripts have been described for the BRCA1 locus [12], there were no signs of aberrant splicing of exon 23 among the 30 normal controls in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…For the 4 studies that reported BRCA mutation in patients with HR+/HER2- breast cancer, none was in the same population in terms of criteria used to select patients. One of the studies required patients to fulfill a complex set of selection criteria in accordance with the National Medical Insurance Reimbursement in South Korea,15 and another only included females with early breast cancer 46…”
Section: Resultsmentioning
confidence: 99%
“…“Basal-like” tumors are characterized by overexpression of genes associated with basal epithelium and proliferation and minimal to no expression of genes associated with estrogen receptor (ER) and human epidermal growth factor receptor 2 (HER2). This gene expression profile is reflected in the immunohistochemical expression of basal markers including cytokeratin 5/6 and epidermal growth factor receptor (EGFR), in addition to lack of expression of ER and progesterone receptor (PR) as well as HER2 ( 27 , 32 35 ). Metaplastic carcinomas have also been reported in BRCA1 mutations carriers ( 36 , 37 ).…”
Section: Hboc-associated Breast Cancermentioning
confidence: 99%